Bio-electrical current response is associated with psychomotor speed in top level soccer player - Hautala, A. J.; Roivainen, E.; Kiviniemi, A. M.; Tulppo, M. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Psychomotor speed has been used to monitor athletes training load and it has been proposed that psychomotor slowness is an early marker of overtraining (Nederhof et al., 2007). However, non-invasive home-based tools to evaluate the training status and recovery of neuromuscular function are missing. Therefore, the purpose of the present study was to examine if a new method, based on bio-electrical current response (BECR), measured at home is associated with psychomotor speed and endurance performance in top level soccer players. Methods: Fourteen Finnish top level soccer players (team AC Oulu, age 21±5, BMI 24±1 kg/m2) performed an endurance fitness test (20m Multistage Fitness Test: BEEP Test) in the field conditions. After the fitness test training load for the players was minimized for one week. During this week psychomotor speed tests (Vienna Test System, SCHUHFRIED GmbH, Austria) with visual warning signals were performed in the laboratory. The inspection and motor phases of reaction time to a visual signal were analyzed. BECR (FAM Sports, Finland) was recorded at same time at home on three separate mornings immediately after wake-up, three times at each measurement session, from left hand with low frequency stimulation. Altogether nine measurements of BECR were averaged for final analyses. Results: The average running time in the BEEP test was 16.6±1.4 min (range 14.1-18.4). Inspection time to visual signal varied from 109 to 212 ms (144±27), motor time from 79 to 223 ms (116±38) and BECR from 3 to 17 mA (6±4). BECR correlated positively with motor time (r= 0.73, p=0.003) and showed a trend of association with inspection time (r= 0.49, p=0.076), BEEP test (r= -0.46, p=0.102) and age (r= 0.41, p=0.148). There was no association between BECR and BMI (r= 0.07, p= ns). Discussion: Bio-electrical current response measured at home is associated with psychomotor speed, particularly motor time to visual warning signal. If the response to electrical stimulus is delayed, motor time is slower. It appears that bio-electrical current response method is a promising tool to evaluate neuromuscular status of soccer players at home conditions during training and recovery.